The Effect of Using ChatGPT as a Learning Technology on EFL Students’ Vocabulary Mastery - Shahdid Siswanto; Akhmad Ali Mirza; Zaitun Qamariah (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Among the core components of learning a language is the vocabulary, which is necessary to learn English. Unfortunately, a lot of EFL students have trouble mastering vocabulary since it's hard to grasp and remember, they don't have enough exposure to it, they don't use effective learning methodologies, and there isn't enough interesting media. The main goal of this study to measure the effect of ChatGPT as a learning technology on EFL students’ vocabulary mastery. This research employed quantitative research using a quasi-experimental research approach. The study was conducted in class XII of Madrasah Aliyah Darul Ulum Palangka Raya. The sample involved a total of 50 students consist of two classes, with class XII-A in total of 26 students as the experimental group and class XII-B in total of 24 students as control group. The learning module was created by the researcher, who also conducted the treatment and analyzed the results of the pre-test and post-test. The findings indicated that ChatGPT significantly affected students' vocabulary mastery. The statistical results showed a t-value of -4.233 and a p-value of 0.000 (< 0.05), which confirmed that ChatGPT had a significant effect. This suggests that integrating ChatGPT into English learning can enhance students’ engagement, motivation, and independence in mastering vocabulary.